Secrets of Success in a Landscape of Fear: Urban Wild Boar Adjust Risk Perception and Tolerate Disturbance - Stillfried, Milena; Gras, Pierre; Börner, Konstantin; Göritz, Frank; Painer, Johanna; Röllig, Kathleen; Wenzler, Moritz; Hofer, Heribert; Ortmann, Sylvia; Kramer-Schadt, Stephanie (Frontiers in Ecology and Evolution, 2017)
1 Introduction The landscape of fear describes an animal’s trade-off between access to food and predator avoidance on a spatial scale (Brown et al., 1999;Laundre J. W. et al., 2010;Laundre et al., 2014). The concept includes that the landscape of fear represents relative levels of predation risk as peaks and valleys that reflect the level of fear in different parts of its area of use (Laundre J. W. et al., 2010). Disturbance of wildlife by people is particularly frequent in urban environments and can exceed disturbance by natural predators. It therefore has the potential to shape prey behavior and should incite avoidance of such environments (Frid and Dill, 2002;Ciuti et al., 2012;Rosner et al., 2014;Stoen et al., 2015). The number of mammals living in urban environments increases (Bateman and Fleming, 2012;Magle et al., 2012). Hence, urban environments can support wildlife and provide various food sources: natural food (Stillfried et al., 2017b) or anthropogenic, easily accessible food (Cahill et al., 2012;Murray et al., 2015;Theimer et al., 2015;Tryjanowski et al., 2015), both of which can contain a high amount of energy (Ottoni et al., 2009;Maibeche et al., 2015). The urban landscape of fear should be worse than the rural one because the threat increases with human proximity per se, a high traffic volume and additional predators such as domestic dogs and other companion animals (Frid and Dill, 2002;Baker et alKinney, 2002;Lowry et al., 2013). Urban wildlife needs to perceive spatio-temporal variation in risk (Valeix et al., 2012). The urban landscape of fear should correspond to landscape features such as roads, because of vehicle and pedestrian traffic (Dowding et al., 2010;Bonnot et al., 2013;Lowry et al., 2013;Morelle et al., 2013;Murray and St Clair, 2015;Thurfjell et al., 2015;Gray et al., 2016), sealed built-up areas (= areas with a high density of housing (Bonnot et al., 2013;Magle et al., 2014;Beninde et al., 2015;Gray et al., 2016) and